The role of inspection in identifying and disclosure of good practice teaching - Ruíz Salmerón, Juan José; Soria Rodríguez, Francisco J. (Avances en Supervisión Educativa, 2014)
The role of school inspection in the exchange of experience between centers serving the same population in a given geographical environment has an impact that does not adhere to the benefits to a particular area but, inevitably shows good educational practices that reverse in improving the learning processes of the entire community.The experience in the Nijar area as a commendable example of commitment of the management teams and the vast majority of teachers, in implementing a job in Education Network is displayed. The experience is getting a remarkable degree of success in participation, involvement and enthusiasm, which is affecting the improvement of school performance.
Keywords: student exchange; inspection; quality of education; good practice